Mechanisms for permeability modification in the damage zone of a normal fault, northern Perth Basin, Western Australia - Olierook, H.; Timms, Nicholas Eric; Hamilton, P. (Elsevier, 2014)
Faults and their associated damage zones in sedimentary basins can be sealing, impeding fluid flow and creating permeability barriers, or open, creating fluid pathways. This impacts the reservoir potential of rocks in fault damage zones. Stylolitization and fracturing severely impacted permeability through compartmentalization and cementation of Apium-1, an exploration hole drilled in the northern Perth Basin, Western Australia. Apium-1 is located 1 km into the hanging wall block damage zone of a major NNW-trending normal fault. The drill core consists of fine- to medium-grained quartz arenite overlain by a coarse-grained lag and capped by impermeable shale. It was quantitatively characterized by sedimentary and structural logging, and microstructural and porosity-permeability analysis. Fractures and stylolites in the damage zone of the major fault are shown to have been sealed. Extensional cracks have been sealed by quartz precipitation; shear fractures that locally preserve brecciation are always quartz and siderite cemented; stylolites are common and contain halos of quartz cementation. In each case, porosity was reduced to approximately 1%, with concomitant reduction of permeability to <<0.01 mD. These structures are observed to be interconnected in the core and are likely to form a larger-scale 3D network of steeply-dipping fractures and shallowly-dipping stylolites. The bulk permeability of the damage zone would reflect the permeability of the fractures and stylolites, compartmentalizing the Mesozoic rocks in the northern Perth Basin into elongate NW-SE trending blocks if the magnitude of stress does not exceed the cemented rock strength.